2022
DOI: 10.1016/j.neo.2021.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effiacy of T cells expressing chimeric antigen receptor derived from a mesothelin-specific scFv in orthotopic human pancreatic cancer animal models

Abstract: Novel CAR T cells targeting mesothelin (MSLN) expressed on pancreatic cancer cells were developed to overcome the limit of the clinical efficacy of CAR T cell therapy for pancreatic cancer patients. Optimal single-chain variable fragments (scFv) binding to MSLN were selected based on the binding activity and the functional effectiveness of various scFv containing CAR-expressing T cells. Engineered MSLN CAR T cells showed successful anti-tumor activity specific to MSLN expression level. Furthermore, MSLN CAR T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The tumor microenvironment (TME) plays a crucial role in the development and progression of HCC, with distinct immune features correlating significantly with response to immune therapy and tumor behavior [ 34 ]. INTS12, for instance, has been identified as a participant in the immunotherapy process for pancreatic cancer [ 35 ]. In this study, we analyzed the correlation between INTSs expression and TME scores, tumor immune cell infiltration, and immune subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME) plays a crucial role in the development and progression of HCC, with distinct immune features correlating significantly with response to immune therapy and tumor behavior [ 34 ]. INTS12, for instance, has been identified as a participant in the immunotherapy process for pancreatic cancer [ 35 ]. In this study, we analyzed the correlation between INTSs expression and TME scores, tumor immune cell infiltration, and immune subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…CAR T cell therapy, which targets both MSLN and CD19 simultaneously, proved to be a safe and well-tolerated approach in treating individuals suffering from metastatic PDAC [ 298 ]. In orthotopic animal models of human pancreatic cancer, it was demonstrated that MSLN-specific CAR T cells are efficient [ 299 ]. Mice with extremely aggressive PDAC experience tumor shrinkage when subjected to a mixture of MSLN-redirected CAR T cells and TNF-α/IL-2-armed oncolytic adenoviruses [ 300 ].…”
Section: Immunotherapeutic Approaches In Pancreatic Cancer Treatmentmentioning
confidence: 99%
“…Afterward, chimeric receptors were able to bind to their specific ligands in the tumor cells and trigger the signal activation for activating CD8+ T cells and releasing cytokines, chemokines, and proteases [ 103 ] ( Figure 5 A). This type of therapy was one of the most promising, with several clinical trials in development, including for pancreatic cancer [ 141 , 142 ], ovarian cancer [ 143 ], and leukemia, in which CAR T cells were directed against targets such as CD70 [ 144 , 145 ] and CD19 [ 146 , 147 ] ( Table 2 ).…”
Section: Single-chain Variable Fragments (Scfv)mentioning
confidence: 99%